Parathyroid hormone ameliorates temporomandibular joint osteoarthritic‐like changes related to age. (10th March 2020) - Cui, Chen; Zheng, Liwei; Fan, Yi; Zhang, Jun; Xu, Ruoshi; Xie, Jing; Zhou, Xuedong
Abstract: Objectives: Ageing could be a contributing factor to the progression of temporomandibular joint osteoarthritis (TMJ OA), whereas its pathogenesis and potential therapeutic strategy have not been comprehensively investigated. Materials and methods: We generated ageing mouse models (45‐week and 60‐week; 12‐week mice as control) and intermittently injected 45‐week mice with parathyroid hormone (PTH(1‐34)) or vehicle for 4 weeks. Cartilage and subchondral bone of TMJ were analysed by microCT, histological and immunostaining. Western blot, qRT‐PCR, ChIP, ELISA and immunohistochemical analysis were utilized to examination the mechanism of PTH(1‐34)'s function. Results: We showed apparent OA‐like phenotypes in ageing mice. PTH treatment could ameliorate the degenerative changes and improve bone microarchitecture in the subchondral bone by activating bone remodelling. Moreover, PTH inhibited phosphorylation level of Smad3, which can combine with p16 ink4a gene promoter region, resulting in reduced senescent cells accumulation and increased cellular proliferation of marrow mesenchymal stem cells (MSCs). ELISA also showed relieved levels of specific senescent‐associated secretory phenotype (SASP) in ageing mice after PTH treatment. Conclusions: In summary, PTH may reduce the accumulation of senescent cells in subchondral bone by inhibiting p16 ink4a and improve bone marrow microenvironment to active bone remodelling process, indicating PTH administration could be a potential preventative and therapeutic treatment for age‐related TMJ OA.